Advancing Energy Storage and Conversion with Ti3C2Tx MXene-Based Flexible Two-Dimensional Hybrid Nanomaterials - Shrivastava, Dr. Shilpi; Shahi, Dr. Sanyogita (Migration Letters, 2023)
Enhancing efficiency in current energy systems necessitates the development of novel materials for energy storage and conversion. The MXene, known as Ti3C2Tx, has gained recognition for its exceptional characteristics, which include elevated conductivity, flexibility, and a substantial surface area. It has garnered considerable attention as a prospective contender for various energy-related applications, including supercapacitors, lithium-ion batteries, photocatalysis, and sensors. The synthesis, scalability, and process integration of Ti3C2Tx MXene present notable obstacles within conventional approaches. This study shows a Ti3C2Tx MXene-based flexible Two-Dimensional Hybrid Nanomaterials (TMF2DHNM) as a solution to address the challenges. This innovative technique aims to enhance energy storage and conversion applications significantly. The TMF2DHNM has remarkable characteristics, such as a specific capacitance of 62.51 F/g, a capacity of 268.53 mAh/g, lithium (Li) element concentration of 216.65 parts per million (ppm), and an average particle size distribution of 15.30 μm. The results demonstrate the exceptional performance of TMF2DHNM compared to currently available techniques, hence establishing a new standard for energy materials. The TMF2DHNM shows a progression within the discipline, establishing a foundation for developing future energy technologies that exhibit enhanced efficiency and sustainability.